Effective Removal of Colour and Toxicity of Textile and Leather Dyes Using Low Cost Biosorbents - Ismail, A. Mohamed; Loganathan, M.; AgastianTheodor, P. (Chemistry and Biochemistry: Research Progress Vol. 1, 2025)
The main objective of this study was to identify, select and utilize various low-cost natural adsorbents such as Prawn shell waste, Rice husk, Poultry soil waste, Apricot seed and Tea powder waste as biosorbents to reduce the colour and toxicity of Textile dye Levafix Blue CA and Leather dye Brown VBR in an eco-friendly approach. The textile dye Levafix Blue CA and leather dye Brown VBR were prepared in the concentration of 500 mg/L as stock solution. The different initial dye concentrations, 100, 200, 300, 400 and 500 mg/L, were prepared from stock solution by diluting with distilled water. Different Biosorbents used in this study were mixed with each dye for every concentration and were agitated and then subsequently removed by centrifugation for decolorization. The adsorbents treated, untreated textile and leather dyes were tested for the growth of P. putida and B. subtilis to evaluate their toxic effects. The formations of colonies on treated dyes indicated that the toxicity was reduced and non-formations of colonies on untreated dyes indicated that no toxicity was reduced. The result showed that the adsorption and decolorization capacity of the biosorbents were in the following order prawn shell waste>rice husk>poultry soil waste>apricot seed>tea powder waste.